Господарсько-правові аспекти реформування правового регулювання принципів державної технологічної політики в умовах воєнного стану - Давидюк, О. (НДІ ПЗІР НАПрН України, 2023)
Недосконалість державного регуляторного впливу стала однієї із тих причин, через які бізнес структури та суб’єкти господарювання вступають у зносини з метою створення, передачі прав та втілення технологій. Незавершеність державної політики у цій сфері, не дозволяє за рахунок регуляторного впливу, компенсувати і ті економічні неспроможності, що виникли внаслідок введених обмежень військового часу через відкриту збройну агресію сусідньої держави. Роботу присвячено дослідженню стану господарсько-правового регулювання принципів державної технологічної політики. Вивчається як рівень відповідності положень чинного законодавства України вимогам та потребам учасників відносин трансферу технологій так і формуються перспективи подальшого вдосконалення вказаних нормативних приписів. Особливу увагу приділено засадам функціонування державної технологічної політики в умовах воєнного стану. Будь-яка державна політика, в тому числі і державна політика у сфері обігу технологій (державна технологічна політика), повинна мати наступну структуру: 1) мета державної політики (тобто те заради чого держава втручається в діяльність суб’єктів господарювання та певні економічні відносини. Ті цілі, досягнення яких є покладається в основу регуляторних дій органів державної влади); 2) завдання державної політики (це стратегічні та середньострокові конкретизовані цілі, досягнення яких визначено в якості орієнтуючих критеріїв, для органів державної влади); 3) об’єкти державної політики (це ті види суспільних відносин, які підпадають під регуляторний вплив держави і вплив на які визначається цілями і завданнями державної політики); 4) принципи державної політики (ті основоположні засади на яких вона базується і які дозволяють забезпечити стабільність і спрямованість актів регуляторного характеру, які приймаються органами державної влади на виконання покладених на них завдань); 5) засоби державної технологічної політики (заздалегідь визначені способи, прийоми, дії, за допомогою яких органи державної влади, від імені держави Україна, втручаються в економічні відносини трансферу технологій). У висновках статті запропоновано авторську концепцію засад (принципів), на яких має відбуватися регуляторний вплив держави у сфері трансферу технологій. Problem setting. The imperfection of state regulatory influence has become one of the reasons why business structures and business entities enter into communication for the purpose of creating, transferring rights and implementing technologies. The incompleteness of state policy in this area does not allow, due to regulatory influence, to compensate for those economic failures that arose as a result of the imposed restrictions of wartime due to the open armed aggression of a neighboring state. Analysis of recent researches and publications. General issues of state intervention in the sphere of the national economy were considered by many scientists. Their numerous achievements formed the basis of regulatory regulation of these processes. Among all the scientists and their achievements, I would especially like to single out V. K. Mamutov, D. V. Zadykhailo, Yu.E. Atamanova, etc. Target of the research is to form an integral system of principles of regulatory regulation of methods, techniques and actions which should be carried out by public authorities to ensure an appropriate level of state regulation in the field of technology transfer, and also to underlie the forms, methods and techniques of influence which should be implemented by the state to eliminate economic inadequacies of the technology market, including those caused by the introduction of martial law and open armed aggression of a neighboring state. Article’s main body. Any state policy, including state policy in the field of technology circulation (state technology policy), should have the following structure: (1) The purpose of state policy (that is, the purpose of which the state intervenes in the activities of economic entities and certain economic relations. Those goals, the achievement of which is the basis of regulatory actions of state authorities); (2) Tasks of state policy (these are strategic and medium-term specific goals, the achievement of which is defined as guiding criteria for state authorities); (3) Objects of state policy (these are the types of social relations that fall under the regulatory influence of the state and the impact on which is determined by the goals and objectives of state policy); (4) Principles of state policy (those fundamental principles on which it is based and which allow to ensure the stability and orientation of acts of a regulatory nature, which are adopted by state authorities to fulfill the tasks assigned to them); 5) Means of state technological policy (predetermined methods, techniques, actions by which state authorities, on behalf of the state of Ukraine, intervene in the economic relations of technology transfer). Conclusions and prospects for development. (1) The author’s concept of the bases (principles) on which the regulatory influence of the state should take place in the field of technology transfer is proposed. (a) Means of state policy in the field of technology circulation should be implemented exclusively on the basis of pre-determined priority areas of implementation of activities related to the implementation of new technologies, at the national, regional, local levels, as well as in a specific industry (s); (b) All measures of the state technological policy must be implemented in accordance with previously formed national, regional, local and industry programs for the implementation of new technologies; (c) State technological policy should be oriented towards the creation of a legal framework and economic mechanisms to support and stimulate the implementation of new technologies; (d) Inviolability of rights to technology and prohibitions on unjustified deprivation of rights to it; (e) Protection of the rights and legitimate interests of subjects of technological activity and provision of an effective system of ways to restore violated rights and legitimate interests; (e) Implementation of measures of financial support and stimulation of projects on the implementation of new technologies; (j) Stimulation of commercial banks and other financial and credit institutions that lend to the implementation of projects related to the implementation of new technologies; (g) Establishing a preferential taxation regime for subjects implementing new technologies; (h) Support for the functioning and development of the infrastructure of the technology market. (1) It is substantiated that for the period of wartime restrictions, the specified system of principles of state technology policy should be supplemented with the following principles: (a) the principle of admissibility of paid withdrawal of rights to technology; (b) the principle of priority for the national use of technology (exclusively on the territory of Ukraine, or for the needs of business entities resident in Ukraine).
Keywords: правове регулювання обігу технологій; трансфер технологій; інноваційна діяльність; державна технологічна політика; legal regulation of technology circulation; technology transfer; innovation activity; state technological policy